Factor influence pre-marital pregnancy in Yogyakarta, Indonesia: a qualitative study - Endang Koni Suryaningsih; Meei Ling Gau (Journal of Health Technology Assessment in Midwifery, 2021)
Getting pregnant before married will raise the multifaceted consequence that can affect to the maternal mental health. In Indonesia, the incident stigmatized as the negative event and particularly, female, will have insecure feeling in their own family as well as in the community. However, the studies have been recognized the predictors of getting pregnant before married among adult. This study aimed to explore the predictors of unwanted pregnancy among Indonesian adults. Qualitative approach has been established and in-depth interview has been applied.